INFLUENCE ANEMIA OF THE EVENT PREECLAMSIA IN MATERNAL - Eka Ameliai; Maryati Sutarno (Science Midwifery, 2022)
Based on data from the Health Office of Serang Banten City, the Maternal Mortality Rate (MMR) in 2017 was 139/100,000 live births, in 2018 it increased to 158/100,000 live births. The causes of maternal death include bleeding 33% and preeclampsia/eclampsia 22%. One of the indirect causes of maternal mortality is anemia pregnancy. Anemia of pregnancy be marked with hemoglobin rate in lower 11g% resulting in placental ischemia. Placental ischemia is a one reason happening preeclampsia. Based on the foregoing, the researcher is interested in conducting a study entitled "The Effect" Anemia of Preeclampsia Incidence in Maternal Maternity at the Bhayangkara Police Hospital Banten in 2021". To know the effect of anemia in pregnancy on the occurrence of preeclampsia in pregnant women. Type of study observational analytic, with case design example. A sample 346 respondents consist of 173 group case and 173 group control. Data analysis used chi-square, odd ratio. Proportion group case which experience anemia is more big than group control. The results of the analysis showed that there was a significant effect between anemia pregnancy with incident preeclampsia p-value 0.000. Risk of preeclampsia on mother maternity which experience anemia pregnancy increase 2,794 time compared to pregnant women who do not suffer from anemia of pregnancy. It is hoped that health workers can detect early risk factors to the possibility of happening preeclampsia, so that capable of collaborating by effective with the medical team for preventive management which is adequate.